(-a) x (-b) = -ab

a x b = ab

ab + (-ab) = 0

a≤

4ab -ab = 3ab

 

Beweise

Beispiele


      -b               -b               -b

-b                -b                -b

-b                -b                -b

-b                -b                -b

      -b               -b               -b


b                 b                 b

       b                  b                  b

       b                  b                  b

       b                  b                  b

b                 b                 b


      -b

  b      -b

  b      -b

-b       b

       b

(-3b) x (-4b) = -12b2

3b x 4b = 12b2

3b x (-4b)

undefiniert!


         -       -       -       -       -       -

   -       -       -       -       -       -

-       -       -       -       -       -

   -       -       -       -       -       -

         -       -       -       -       -       -


         -

  +   -   +

  +   +   -

  -   +   -

         +

 

 

(-a) x (-a) = -a2

a x a = a2

Elimination/Vermischung,
deshalb undefiniert!


+       +       +       +       +       +        

+       +       +       +       +       +  

+       +       +       +       +       +

+       +       +       +       +       +  

+       +       +       +       +       +